Integrated Approach to Investigate the Effect of Leachate on Groundwater around the Ikot Ekpene Dumpsite in Akwa Ibom State, Southeastern Nigeria - N. J. George; A. I. Ubom; J. I. Ibanga (International Journal of Geophysics)
Geophysical, geochemical, and hydrogeological measurements have been integrated to assess the effect of leachate on groundwater quality within the dumpsite in Ikot Epene Local Government Area of Akwa Ibom State, Southern Nigeria, and its environs. The resistivity values and depth of burial of the geomaterials, constrained by geology, were used in producing resistivity cross sections which show the geoelectric distribution of the subsurface near and away from the dumpsite. The observed high conductivity in subsurface layers closed to the dumpsite is symptomatic of the leachate-loaded conductive fluid leached and drained into the subsurface. The hydrochemical results of some species conform to WHO standards, while some were found to be relatively higher due to dissolution, leaching, and draining of leachate related contaminants in the soil. The correlation indices of the ion pairs show no significant effect on the paired ions, indicating that the significant value of some of the individual ions is not geologic but due to precipitation from the leachate residue. In general, the effect of leachate is more dominant in the immediate groundwater pathway near the dumpsite than aquifer repositories away from it. The crossplots of the water resistivity and bulk resistivity show exponential increase for the different layers.